2018
DOI: 10.1186/s12978-018-0467-x
|View full text |Cite
|
Sign up to set email alerts
|

Warning about drinking during pregnancy: lessons from the French experience

Abstract: BackgroundIn France, since 2007, there is a compulsory warning recommending abstinence during pregnancy on every container of alcohol. Awareness of this warning, which consists of a small pictogram, is unknown. The aim of this study was to assess awareness of the warning and risk perceptions about prenatal drinking in pregnant and postpartum women.MethodsA cross-sectional survey was carried out by telephone five years after the introduction of the warning label. A total of 3603 pregnant or postpartum French wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
0
20
0
3
Order By: Relevance
“…Research on risk perception of alcohol consumption among pregnant women is scarce, particularly in the Mediterranean countries of Europe, which have traditionally been characterized by a high level of alcohol consumption (among women as well). Specifically, almost no research has been done on whether this perception varies as a function of the type of drink (beer, wine, or liquor) in question [30].…”
Section: Introductionmentioning
confidence: 99%
“…Research on risk perception of alcohol consumption among pregnant women is scarce, particularly in the Mediterranean countries of Europe, which have traditionally been characterized by a high level of alcohol consumption (among women as well). Specifically, almost no research has been done on whether this perception varies as a function of the type of drink (beer, wine, or liquor) in question [30].…”
Section: Introductionmentioning
confidence: 99%
“…The model identifies the perceived risk of drinking wine while pregnant as another predictor of alcohol consumption during pregnancy, in the sense that might be expected: The lower the perceived risk, the greater the consumption (estimated in grams of pure alcohol). Studies carried out in Australia [50], France [16], and Spain [32] found that low perception of the risks posed by consuming wine while pregnant dominates among expectant mothers. In Spain (and perhaps in other social contexts where low perception of the potential teratogenic effects of this alcoholic beverage dominates), it is precisely those expectant mothers who are most aware of the adverse effects on the fetus who present lower alcohol consumption during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…With the passing of time, since it has not been possible to establish that there are safe levels of alcohol consumption during pregnancy, and at the same time, since there is increasing evidence that low levels of alcohol consumption can lead to risks to fetal development [15], there are many countries where official health guidelines on pregnancy recommend abstaining completely from drinking alcohol during this time. Thus, since 2002, France has recommended total abstention from alcoholic beverages during pregnancy [16]. National public health bodies in Australia [17], Denmark [18], and Norway [19] have made equivalent recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Misconceptions about the safety or supposed health benefits of different types of alcoholic drink are common, whether in the context of pregnancy, [18, 19] or in the general population [20]. Further, it is well established that there are many misconceptions about the ‘standard alcoholic drink’.…”
Section: Discussionmentioning
confidence: 99%